Inter - departmental Student Projects – Challenges and Benefits - Geetha Kiran, A.; Mohana Lakshmi, J.; Nanditha, B. R.; Swathi, H. Y. (Journal of Engineering Education Transformations, 2018)
Our educational policy fosters young students to have broad perspective, high level expertise and logicality. The education system is not coping up with the same pace as technology changes are happening. Therefore, it is essential to tackle this situation with new ideas and adapt education to the changing needs. The interdepartmental educational programmes have already met new academic needs. Reinforcing this standpoint a unique approach on interdepartmental collaborative learning has been initiated by the department of Information Science &Engineering and Electrical&Electronics Engineering, Malnad College of Engineering, Hassan. This approach aims in promoting wide inter-department learning process where students from two different departments are conjoined to venture interdisciplinary projects. The students of 3rd semester from both the departments were allowed to choose a particular domain of their interest and design prototypes for various applications. As a back - end support, the subject experts jointly nurtured the ideas of students and helped them to give a practical shape to their ideas. Further, adding a hardware component offered an opportunity to increase student engagement by strengthening programming concepts with relevant hardware projects. This process helped the students to work together in different domains learning new interesting solutions for different problems and has provided mutual beneficial results.